The impact of economic recessions on health workers: a systematic review and best-fit framework synthesis of the evidence from the last 50 years. Issue 4 (4th January 2021) - Russo, Giuliano; Silva, Tiago Jesus; Gassasse, Zakariah; Filippon, Jonathan; Rotulo, Arianna; Kondilis, Elias
Abstract: Economic crises carry a substantial impact on population health and health systems, but little is known on how these transmit to health workers (HWs). Addressing such a gap is timely as HWs are pivotal resources, particularly during pandemics or the ensuing recessions. Drawing from the empirical literature, we aimed to provide a framework for understanding the impact of recessions on HWs and their reactions. We use a systematic review and best-fit framework synthesis approach to identify the relevant qualitative, quantitative and mixed-methods evidence, and refine an a priori, theory-based conceptual framework. Eight relevant databases were searched, and four reviewers employed to independently review full texts, extract data and appraise the quality of the evidence retrieved. A total of 57 peer-reviewed publications were included, referring to six economic recessions. The 2010–15 Great Recession in Europe was the subject of most (52%) of the papers. Our consolidated framework suggests that recessions transmit to HWs through three channels: (1) an increase in the demand for services; (2) the impacts of austerity measures; and (3) changes in the health labour market. Some of the evidence appeared specific to the context of crises; demand for health services and employment increased during economic recessions in North America and Oceania, but stagnated or declined in Europe in connection with the austerity measures adopted. Burn-out, lay-offs, migration and multiple jobholding were the reactions observed in Europe, but job opportunities never dwindled for physicians during recessions in North America, with nurses re-entering labour markets during such crises. Loss of motivation, absenteeism and abuse of health systems were documented during recessions in low-income countries. Although the impacts of recessions may vary across economic events, health systems, labour markets and policy responses, our review and framework provide an evidence base for policies to mitigate the effects on HWs.